Let algorithm A1 be defined by: = 2 if i >= 0 and j = 0. a(i,j) = i + 2 if i >= 0 and j = 1. = (i+2) * a(i,j-1) - a(i,j-2) if i >= 0 and j > 1. Let algorithm A2 be defined by: Let r1 and r2 be the roots of x + 1/x = k, for k an integer. Note that r1 + r2 = k, and r1 * r2 = 1. Define f(k,n) = r1^n + r2^n, for integers k >= 1 and n >= 0. Theorem. a(i,j) = f(i+2,j) for i,j >= 0. Proof. The proof shows that for a given value of i, the sequences a(i,0), a(i,1), . . . , a(i,j), . . . and f(i+2,0), f(i+2,1), . . . , f(i+2,j), . . . and are identical. Cases 1 and 2 establish the basis. Case 3 is the induction step on j. Case 1. j = 0: f(i+2,0) = 2 = a(i,0). Case 2. j = 1: f(i+2,1) = r1 + r2 = k = i + 2 = a(i,1). Case 3. j > 1. Assume that a(i,m) = f(i+2,m) for 0 <= m < j. Begin with a tautology of the form (a+b)*(c+d) = a*c + b*d + b*c + a*d. (r1 + 1/r1) * (r1^(j-1) + 1/r1^(j-1)) = r1^j + 1/r1^j + r1^(j-2) + 1/r1^(j-2) Since r2 = 1/r1, we have (r1 + r2) * (r1^(j-1) + r2^(j-1)) = r1^j + r2^j + r1^(j-2) + r2^(j-2) but this is (in general) k * f(k,j-1) = f(k,j) + f(k,j-2) or (in this specific case) (i+2) * f(i+2,j-1) = f(i+2,j) + f(i+2,j-2). Hence f(i+2,j) = (i+2) * f(i+2,j-1) - f(i+2,j-2) which, by the induction hypothesis, is (i+2) * a(i,j-1) - a(i,j-2) = a(i,j). Joseph Kirtland Marist College Poughkeepsie, NY March 12, 2018